Performance and sustainability analysis of an Organic Rankine Cycle system in subcritical and supercritical conditions for waste heat recovery - Saadon, Syamimi; Mohd Nasir, Nur Athirah (Multidisciplinary Digital Publishing Institute, 2020)
This study addresses the performance analysis of a subcritical and supercritical Organic Rankine Cycle (ORC) with the addition of a preheater or superheater integrated with a turbofan engine. This analysis will try to explore the heat transfer throughout the evaporator for the purpose of determining the ORC output power and thermal efficiency. A simplified numerical model of the ORC for waste heat recovery is presented. The model depicts the evaporator by using a distributed model, and includes parameters such as the effectiveness, heat capacity and inlet temperature of the waste heat and the organic fluid. For a given set of initial parameter values, the output power and thermal efficiency, as well as the mass flow rate of the working fluid are acquired by solving the system’s thermodynamic cycle with the aid of MATLAB software. The model is then verified by using data from an industrial waste heat recovery system. The connection between the turbofan engine and the ORC system was established and evaluated by means of Thrust-Specific Fuel Consumption (TSFC) as well as fuel burn. It was found that the supercritical ORC with a preheater and superheater exhibits lower TSFC than the subcritical ORC, whereas the impact of the ORC in terms of waste heat recovery in relation to the environment and sustainability indices is quite small, but still considerable depending on the engine’s weight.